Protective Effect of Bruguiera gymnorrhiza (L.) Lam. Fruit on Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice: Role of Keap1/Nrf2 Pathway and Gut Microbiota - Lin, Yinsi; Zheng, Xinghan; Chen, Jinfen; Luo, Dandan; Xie, Jianhui; Su, Ziren; Huang, Xiaoqi; Yi, Xiaoqing; Wei, Long; Cai, Jian; Sun, Zhanghua (Frontiers in Pharmacology, 2020)
Bruguiera gymnorrhiza (BG), a medicinal mangrove, and its fruit (a food material), have traditionally been used to treat diarrhea (also known as ulcerative colitis) in folk medicine. However, the mechanism of action against colitis remains ambiguous. This study aimed to investigate the potential efficacy and mechanism of BGF on experimental colitis. Colitis was induced by oral intake of dextran sulfate sodium (DSS) and treated with aqueous extract of BGF (25, 50 and 100 mg/kg) for a week. The disease activity index (DAI), colon length and histological changes of colon were analyzed. The inflammatory and oxidative stress status was explored. The protein expression of Nrf2 and Keap1 in the colon was detected by Western blotting. The mRNA expression of Nrf2 downstream genes (GCLC, GCLM, HO-1 and NQO1) was determined by RT-PCR. Furthermore, the effect on intestinal flora was analyzed. Results indicated that BGF was rich in pinitol, and showed strong antioxidative activity in vitro. Compared with the DSS model, BGF effectively reduced the body weight loss and DAI, restored the colon length, repaired colonic pathological variations and decreased the histological scores, which was superior to salicylazosulfapyridine (SASP) with smaller dosage. Moreover, BGF not only abated the levels of MDA and inflammatory mediators (TNF-α, IL-6, IL-1β, and IFN-γ), increased the level of IL-10, but also prevented the depletion of SOD and GSH. BGF upregulated the protein level of nuclear Nrf2 and mRNA levels of GCLC, GCLM, HO-1 and NQO1, while significantly inhibited the protein expression of Keap1 and cytosolic Nrf2. Besides, BGF promoted the growth of probiotics (Bifidobacterium, Anaerotruncus and Lactobacillus) in the gut, and inhibited the colonization of pathogenic bacteria (Bacteroides and Streptococcus), which contributed to the maintenance of intestinal homeostasis. BGF possessed protective effect against DSS-induced colitis. The potential mechanism of BGF may involve the amelioration of inflammatory and oxidative status, activation of Keap1/Nrf2 signaling pathway and maintenance of micro-ecological balance of the host. This study provides experimental evidence for the traditional application of BGF in the treatment of diarrhea, and indicates that BGF may be a promising candidate against colitis.